벤처확인유형을 중심으로 한 벤처기업의 성장 분석 - 김기완 (12969, 2013)
‘Venture firms’ in Korea are the firms who are certified as ‘venture’, whose certification types are defined by a law (‘Special Law for the Support of Venture Firms’), and therefore encompass not only the venture capital-financed companies, which ar